Bangladeshi Migrant Workers in Malaysia: Their Socio- Cultural Background and Work-Adaptability - Karim, A.H.M Zehadul; Mohamad Diah, Nurazzura; Mustari, Sohela; Sarker, Md. Shahidul Islam (Serials Publications, 2015)
A large number of migrant workers from Bangladesh come to Malaysia because of having bilateral agreements signed by both governments from time to time since 1992. It is well known that due to some structural national inequality, a bulk of unemployed labor-force from Bangladesh temporarily migrate to many foreign countries including Malaysia seeking temporary employment in different work-organizations. It is of no denying of the fact that what a Bangladeshi worker earns in one month in Malaysia, would take a few months to earn it in back home. Because of having such structural and techno-economic difference the unemployed laborers of Bangladesh often become very much attracted and fascinated to come to Malaysia for searching employment. Based on snowball technique, this baseline survey was conducted in and around Kuala Lumpur city in Malaysia to generate quantitative data from 200 sample-workers. It provided a socio-economic and cultural background and also at the same time, added additional information on the problems and the hurdles that the Bangladeshi workers have to face on their arrival here in Malaysia.